Hepatitis mortality in Brazil and regions, 2001-2020: temporal trend and spatial analysis - Laryssa Fialho de Oliveira Sousa; Evelen Rouse de Souza Santos; Rayssa Mendonça Oliveira; Renata Lima Batalha Andrade; Jefferson Felipe Calazans Batista; Sonia Oliveira Lima (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2023)
ABSTRACT Objective: To analyze the spatial distribution and the temporal trend of the hepatitis mortality rate in Brazil from 2001 to 2020. Methods: Ecological, temporal, and spatial study on mortality from hepatitis in Brazil with data from the Mortality Information System (Sistema de Informações sobre Mortalidade - SIM/DATASUS). Information was stratified by year of diagnosis, region of the country, municipalities (of residence). Standardized mortality rates (SMR) were calculated. The temporal trend was estimated by Prais-Winsten regression and the spatial distribution by the Global Moran Index (GMI). Results: The highest SMR means in Brazil were for Chronic viral hepatitis with 0.88 deaths per 100,000 inhabitants (SD=0.16), followed by Other viral hepatitis with 0.22/100,000 (SD=0.11). In Brazil, the temporal trend of mortality from Hepatitis A was −8.11% per year (95%CI −9.38; −6.82), while for Hepatitis B it was −4.13% (95%CI −6.03; −2.20), of Other viral hepatitis of −7.84% (95%CI −14.11; −1.11) and of Unspecified Hepatitis −5.67% per year (95%CI −6.22; −5.10). Mortality due to chronic viral hepatitis increased by 5.74% (95%CI 3.47; 8.06) in the North and 4.95% in the Northeast (95%CI 0.27; 9.85). The Moran Index (I) for Hepatitis A was 0.470 (p<0.001), for Hepatitis B 0.846 (p<0.001), Chronic viral hepatitis=0.666 (p<0.001), other viral hepatitis=0.713 (p<0.001), and Unspecified Hepatitis=0.712 (p<0.001). Conclusion: The temporal trend of hepatitis A, B, other viral, and unspecified hepatitis was decreasing in Brazil, while mortality from chronic hepatitis was increasing in the North and Northeast.